HUMAN-GEOGRAPHICAL ATTRIBUTES OF RELATIONAL DATABASES OF GEOGRAPHIC INFORMATION SYSTEMS - Сергєєва, Наталія (Human Geography Journal, 2015)
The types of scales for data measurement and data types used to record the attributes of GIS (geographic information systems) relational databases are considered. The table of the interrelation between the scales for data measurement and the data types represented in relational tables of GIS databases is composed. The application of these interrelations for human-geographical attributes recording at the example of the human-geographical maps of GIS-version of The National Atlas of Ukraine is considered. The types of interrelations that are most often used to record human-geographical attributes are analyzed.